Oxidative stability of palm - and soybean-based medium- and long-chain triacylglycerol (MLCT) oil blends - Koh, Soo Peng; Arifin, Norlelawati; Lai, Oi Ming; Yusoff, Mohd Suria Affandi; Long, Kamariah; Tan, Chin Ping (Wiley Interscience, 2009)
BACKGROUND: Medium- and long-chain triacylglyerols (MLCT) enzymatically esterified using Lipozyme RM IM lipase has very low oxidative stability as it does not contain any antioxidants. The aim of this work was to study the ability of various antioxidants to increase the oxidative stability of palm- and soybean-based MLCT blends which assist to bring up the oxidative stability of both MLCT blends. In this study, the effectiveness of rosemary extracts, sage extracts, tert-butylhydroquinone (TBHQ) and mixtures of tert-butyl-4-hydroxyanisole (BHA) and tert-butyl-p-hydroxytoluene (BHT) in protecting against oxidation of various MLCT blends was investigated.